Carbon pricing drives critical transition to green growth - Isaak Mengesha; Debraj Roy (Nature Communications)
Abstract Carbon pricing is a crucial tool in the efforts to address and mitigate climate change. In 2014, only 12% of carbon emissions fell under carbon pricing at USD7 per tonne; now, about 23% of greenhouse gas emissions are priced at USD32 per tonne. However, the regressive nature of carbon pricing can disproportionately affect lower-income populations and potentially reduce political support and public awareness. This raises questions about the dynamics of increasing carbon pricing rates and the optimal balance between inequality, emissions, and economic growth. We find that a critical level of carbon pricing can induce tipping points; incentivizing technological adoption and fuel switching behaviour of energy producers. By combining carbon pricing with redistributive measures at these tipping points, we demonstrate that emissions can be rapidly reduced while maintaining economic growth and decreasing inequality. We also introduce real-time metrics for detecting sector-specific tipping points, without requiring counterfactual analysis. Our research has important implications for the ongoing debate around the relationship between economic growth, inequality, and environmental sustainability.